Roles of Children and Adolescents in COVID-19 Transmission in the Community: A Retrospective Analysis of Nationwide Data in Japan - Imamura, Tadatsugu; Saito, Mayuko; Ko, Yura K.; Imamura, Takeaki; Otani, Kanako; Akaba, Hiroki; Ninomiya, Kota; Furuse, Yuki; Miyahara, Reiko; Sando, Eiichiro; Yasuda, Ikkoh; Tsuchiya, Naho; et al. (Frontiers in Pediatrics, 2021)
Background Roles of children and adolescents in spreading coronavirus disease 2019 (COVID-19) in the community is not fully understood. Methods We analyzed the data of 7,758 children and adolescents with COVID-19 and characteristics of secondary transmission generated by these cases using case information published by local governments. Ratio of pediatric and adolescent cases generating secondary transmission was calculated for various social settings. Results The incidence of COVID-19 was 24.8 cases per 105 population aged between 0 and 9 years, and 59.2 among those aged between 10-19 years, which was lower than that among individuals of all age groups (79.6 per 105 population) between January 15 and October 31, 2020. The proportion of cases generating secondary cases was 8.3% among infants and young children in nursery schools and kindergartens, 16% among children and adolescents attending primary schools, 34% among those attending junior high schools, 43% among those attending high schools, 31% among those attending professional training colleges, and 24% in those attending universities. Households were the most common setting for secondary transmission. Conclusion The risk of generating secondary cases might be limited among pediatric and adolescent cases with COVID-19, especially in settings outside households. Effectiveness of traditional mitigation measures (e.g., school closures) to suppress COVID-19 transmissions should be carefully evaluated.